Wetlands: a flooding solution - Engelke, Jennifer (Kansas State University, 2012)
Wildcat Creek in Riley County, KS has repeatedly flooded in the past 5 years causing significant damage to the watershed, private property, and community livelihood. Strategically placing wetlands throughout the watershed can help reduce stormwater runoff, increase infiltration, and increase wildlife habitat. A watershed assessment was completed to determine the best location for wetlands in the Wildcat Creek Basin. Two watershed-scale plans for wetlands were derived and evaluated based upon estimation of stormwater runoff and quality of wildlife habitat. Wetlands were then examined and incorporated into existing land cover and land uses at the site-scale for an existing golf course. Three proposals for the nine hole course (for best golf experience, wildlife habitat, and wetland creation) were developed to reflect expansion options from a Par 30 to a Par 34 or 35 course. Each proposal was evaluated based on wetland capacity from estimated stormwater runoff, quality of wildlife habitat, playability of the golf course for all skill levels, and cost of implementation. After this evaluation, the wetland proposal was moved forward and further developed into a proposal that is best suited for the site. Following wetland implementation, stormwater runoff can be collected on-site to prevent runoff and flooding at the golf course and downstream. In order to solve flooding problems in the Wildcat Creek watershed, a series of wetlands can be implemented at the smaller site scale, like the Wildcat Creek Golf Course site, throughout the watershed. Wetlands are one component of a larger stormwater management system that is needed to reduce flooding of the Wildcat Creek and the flood-prone area of Manhattan, KS.
Keywords: Wildcat Creek Watershed; Wetlands; Flooding; Golf course; Wildlife habitat; Landscape Architecture (0390)